Commitment decisions with demand information updating and a capital‐constrained supplier. (12th September 2019) - Zhai, Youzi; Xue, Weili; Ma, Lijun
Abstract: In this paper, we study a single two‐echelon supply chain with a capital‐constrained supplier (manufacturer) and a retailer. The supply chain faces a stochastic demand. As the production lead time is long, the market demand is updated during the supplier's production lead time. The supplier needs to determine the production quantity based on the original demand forecast, and the retailer needs to determine the time and quantity to order. The retailer can place an order before the supplier's production (preorder) or after the supplier's production (regular order). We prove the existence of optimal equilibrium solutions under both preorder and regular order strategies. We analytically investigate the order strategies for the supply chain agents under perfect and worthless market information updating. Moreover, we numerically analyze the impact of the information updating quality on the order strategy selection, and the effect of exogenous shocks on the supply chain agents.